A Validation of the Chinese Motivation for Reading Questionnaire. (September 2021) - Wang, Xiaocheng; Jin, Yuanying
This study addressed the cross-cultural validation of the Chinese Motivation for Reading Questionnaire (CMRQ) in a sample of 522 seventh to ninth graders from two public schools in eastern China. Confirmatory factor analyses, item-total correlation analyses, and reliability analyses were conducted to assess the psychometric quality of the CMRQ. The results indicated that the three-factor model for the competence beliefs scale, the six-factor model for the goals for reading scale, and the two-factor model for the social motivation scale fit the data properly. All subscales showed good levels of internal consistency reliabilities, ranging from .71 to .86. The concurrent validity of the CMRQ was supported by significant correlations among subscales with reading attitudes. Students scored the highest on intrinsic motivation, followed by social motivation, competence beliefs, and then extrinsic motivation. The findings further confirmed the existence of several distinguishable dimensions of reading motivation. Finally, implications for literacy research and instruction were discussed.